Daur Ulang Minyak Jelantah: Pengelolaan Limbah Domestik Rumah Tangga melalui Pembuatan Lilin Aromaterapi di Desa Sarirogo, Sidoarjo, Jawa Timur - Budi Prabowo; Raisya Octavia Putri Prianto; Sindi Ayu Antika (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The community service activity program that we carried out entitled MIGUNANI (Processing Used Cooking Oil Waste into Valuable Goods) involving the women of Sarirogo Village, Sidoarjo Regency, East Java was held on August 15, 2024. The purpose of this activity is to reduce the risk of environmental pollution due to used cooking oil waste by processing it into aromatherapy candles. Thus, used cooking oil waste, which can initially pollute the environment, can be turned into valuable goods and can become a business idea for additional income for mothers. The output targets produced are aromatherapy candles and devotion journals. In realizing the output targets, the methods used include socialization, training and direct practice to increase the creativity of participants. The hope of the activity program that we have carried out is that the participants will have knowledge and insight in processing used cooking oil waste into valuable goods and creative business ideas.